Public Exclusion, Under Funding and the Intensification of Work: Universities and the Erosion of Democracy in Ontario - Healy, Teresa (Just Labour, 2003)
As public anxiety over access to education increases, public-sector workers are directly able to perceive the extent to which exclusion, rather than public- access, now characterizes post-secondary education in an era of privatization. This paper will address some of the recent experiences of university workers who are members of the Canadian Union of Public Employees (CUPE). Here we shall identify three issues facing workers in the sector including: i) the privatization of universities through government policy shifts, ii) the employer-led reorganization of work, and iii) university workers’ campaigns to resist and transform these conditions. For public sector workers, decreasing access to social programs, under funding and the intensification of work are very clearly linked. As the restructured state brings public services more fully into the market and increasingly under the direct control of a global capitalist class, democratic rights are eroded. Still, this privatization dynamic is not uni-directional. Public sector workers and their community allies have been part of the history of state restructuring through their conscious acts of resistance, collective bargaining strategies, militancy and coalition-building. À mesure qu’augmente l’inquiétude du public au sujet de l’éducation, le personnel du secteur public est en mesure de constater directement que l’exclusion, plutôt que l’accès du public, caractérise l’éducation postsecondaire en ces temps de privatisation. L’article traite de certaines des expériences récentes de membres du personnel universitaire qui font partie du Syndicat canadien de la fonction publique (SCFP). Il porte plus précisément sur trois problèmes du personnel du secteur public : i) la privatisation des universités à la faveur de la modification des politiques gouvernementales, ii) la réorganisation du travail dirigée par l’employeur, et iii) les campagnes des travailleurs et travailleuses universitaires visant à résister et à transformer ces conditions. Pour le personnel du secteur public, la diminution de l’accès aux programmes sociaux, l’insuffisance du financement et l’intensification du travail sont nettement liées. À mesure que la restructuration de l’État met des services publics sur le marché privé et les place directement sous le contrôle d’une classe capitaliste mondiale, les droits démocratiques s’affaiblissent. La dynamique de la privatisation n’est cependant pas unidirectionnelle. Le personnel du secteur public et ses alliés communautaires ont participé à la restructuration de l’État par leur résistance réfléchie, leurs stratégies de négociation collective, leur militantisme et l’établissement de coalitions.